Answer:
A = 41 in
B = 44 in
Tree = B
Step-by-step explanation:
We can represent the height of Tree A after t years as:
A = 29 + 2t
Because 29 inches is the initial height and 2 is the change in the height every year.
In the same way, we can represent the height of Tree B after t years as:
B = 14 + 5t
Because 14 inches is the initial height and 5 is the change in the height every year.
So, after 6 years, the height of each tree is:
A = 29 + 2(6) = 29 + 12 = 41 in
B = 14 + 5(6) = 14 + 30 = 44 in
Therefore, the taller tree is Tree B.